Late Cretaceous–early Eocene Laramide uplift, exhumation, and basin subsidence in Wyoming: Crustal responses to flat slab subduction. Issue 4 (15th April 2014) - Fan, Majie; Carrapa, Barbara
Abstract Low‐angle subduction of the Farallon oceanic plate during the Late Cretaceous–early Eocene is generally considered as the main driver forming the high Rocky Mountains in Wyoming and nearby areas. How the deformation was transferred from mantle to upper crust over the great duration of deformation ( 40 Myr) is still debated. Here, we reconstruct basin subsidence and compile paleoelevation, thermochronology, and provenance data to assess the timing, magnitude, and rates of rock uplift during the Laramide deformation. We reconstruct rock uplift as the sum of surface uplift and erosion constrained by combining paleoelevation and exhumation with regional stratigraphic thickness and chronostratigraphic information. The amount (and rate) of rock uplift of individual Laramide ranges was less than 2.4–4.8 km ( 0.21–0.32 mm/yr) during the early Maastrichtian‐Paleocene (stage 1) and increased to more than 3 km ( 0.38–0.60 mm/yr) during the late Paleocene–early Eocene (stage 2). Our quantitative constraints reveal a two‐stage development of the Laramide deformation in Wyoming and an increase of rock uplift during stage 2, associated with enhanced intermontane basin subsidence. Exhumation and uplift during stage 1 is consistent with eastward migration of Cordilleran deformation associated with low‐angle subduction, whereas the change in exhumation during stage 2 seems to follow a southwestward trend, which requires an alternative explanation. We here suggest that the increase of rock uplift rate during the late Paleocene–early Eocene and the southwestward younging trend of uplift may be a response to the rollback and associated retreating delamination of the Farallon oceanic slab.